Mechanisms of Cardiomyopathy in Liver Cirrhosis - Lee, Samuel S (Japanese Journal of Portal Hypertension and Esophageal Varices, 1997)
In cirrhosis, the circulation becomes hyperdynamic, characterized as increased baseline cardiac output with decreased arterial pressure and peripheral vascular resistance. Despite the increased basal cardiac output, the heart reacts subnormally when subjected to physiological or pharmacological stress such as exercise, drugs or surgery. This blunted responsiveness of ventricular contractility has been termed “cirrhotic cardiomyopathy, ” but its pathogenesis remains unclear. We aimed to clarify the pathogenic factors underlying this condition, in particular the role of membrane changes in autonomic receptors or their signal transduction pathway, in different rat models of chronic liver disease. The majority of studies were performed in the chronic (4-week) bile duct ligated cirrhotic rat (BDL), a model of biliary cirrhosis with deep jaundice. Other studies were also performed in 3 other models of portal hypertension / cirrhosis were studied : portal vein-stenosed rats with infrahepatic portal hypertension but no parenchymal liver disease (PVS); thioacetamide-induced cirrhotic rats (TA), bile duct ligated cirrhotic rats then subjected to choledochojejunostomy to reanastomose the bile flow and relieve biliary obstruction (BDR) Controls had sham operation. Isolated left ventricular papillary muscles from these groups were tested for β-adrenergic responsiveness by electrical stimulation at 1Hz, voltage 1.3 × threshold, with graded doses of the β-adrenergic agonist isoproterenol. Compared to the sham-controls, muscles from all 3 cirrhotic groups showed blunted isoproterenol responsiveness, while PVS was not different from shams. Cardiac sarcolemmal plasma membranes were prepared from the ventricles of BDL or control rats by sucrose gradient centrifugation. Static and dynamic components of membrane fluidity were assessed by using diphenylhexatriene and stearic acid labelled with a series of 9-anthroyloxy probes, respectively. 3H-dihydroalprenolol and 3H-methyl scopalamine were used as radioligands to respectively characterize the stimulatory β-adrenergic and inhibitory muscarinic (m2) receptors. G-proteins were assessed by fluoride stimulation and SDS-PAGE with western blots using rabbit antibodies to G-protein subtypes. Adenylyl cyclase activity measured by cAMP generation was measured at baseline and following stimulation with 3 compounds : isoproterenol to activate the receptor, NaF to stimulate Gs-protein directly, and forskolin which stimulates adenylyl cyclase independent of receptor activation. BDL and TA rats showed decreased cAMP generation with all 3 drugs, whereas the BDR rats only showed decreases with isoproterenol and NaF, but intact forskolin responses. Compared to controls, the BDL rats had a 15% decrease in the β-adrenoceptor density without any change in the binding affinity. The receptor density and binding affinity of the m2 receptors were unchanged from controls. Despite the unchanged m2 receptor characteristics, isolated left ventricular papillary muscles from BDL rats showed blunted carbacho-induced attenuation of isoproterenol-stimulated contractility, indicating blunting of muscarinic function. Moreover we found a 40% decrease in isoproterenol-stimulated AC activity, suggesting that postreceptor factors in the signal transduction pathway for the β-adrenoceptor are also involved. This was confirmed by the fluoride and forskolin studies which showed attenuated responses, indicating defective Gs and AC enzyme activity in BDL rats. The BDL menbrane content of Gas and Gia as determined by western blotting were decreased by 20% and 47%, while the Gcommob B level was unchanged. Both static and dynamic membrane fluidity significantly decreased, and the membrane cholesterol content was increased in the BDL rats, with consequent increased cholesterol : phospholipid ratio.